GRID COMPUTING IN PAKISTAN: OPENING TO LARGE HADRON COLLIDER EXPERIMENTS - Batool, N.; Osman, A.; Mahmood, A.; Rana, M. A. (The Nucleus, 2020)
A grid computing facility was developed at sister institutes Pakistan Institute of Nuclear Science and Technology (PINSTECH) and Pakistan Institute of Engineering and Applied Sciences (PIEAS) in collaboration with Large Hadron Collider (LHC) Computing Grid during early years of the present decade. The Grid facility â€œPAKGRID-LCG2â€ as one of the grid node in Pakistan was developed employing mainly local means and is capable of supporting local and international research and computational tasks in the domain of LHC Computing Grid. Functional status of the facility is presented in terms of number of jobs performed. The facility developed provides a forum to local researchers in the field of high energy physics to participate in the LHC experiments and related activities at European particle physics research laboratory (CERN), which is one of the best physics laboratories in the world. It also provides a platform of an emerging computing technology (CT).